2022
DOI: 10.21203/rs.3.rs-2015602/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessments of classical dry-blending/moulding and solution casting PVC plasticization effectiveness – a comparative study

Abstract: Plasticizers are the most popular and indispensable plastic additives, facilitating their processability and providing suitable flexibility. Plasticizing efficiency is a term that is used to compare between different types of plasticizers. Plasticizing efficiency can be assessed using specimen fabricated through either a three-stage method consisting of mixing, extruding and pelletizing, or a solution casting method. In this paper, we aim to compare the results of plasticization efficiency assessed for specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…[3][4][5][6][7][8][9] In addition to the traditional methods of mixing PVC and ES [10][11][12][13][14] , composites based on PVC with or without plasticizer can also be obtained by solution casting. 6,[15][16][17][18] A review of the scientific literature showed that there are not many publications on the use of waste eggshells as a biofiller in the production of PVCbased materials. [10][11][12][13][14] For the most part, these studies consider the effect of ES particle size, 12 the degree of filling, 13,14 and the preparation and mixing methods 10,11 on the structure, tensile, and thermal properties of PVC-ES composites.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] In addition to the traditional methods of mixing PVC and ES [10][11][12][13][14] , composites based on PVC with or without plasticizer can also be obtained by solution casting. 6,[15][16][17][18] A review of the scientific literature showed that there are not many publications on the use of waste eggshells as a biofiller in the production of PVCbased materials. [10][11][12][13][14] For the most part, these studies consider the effect of ES particle size, 12 the degree of filling, 13,14 and the preparation and mixing methods 10,11 on the structure, tensile, and thermal properties of PVC-ES composites.…”
Section: Introductionmentioning
confidence: 99%
“…One of the possibilities for improving the qualities of compositions based on PVC is mixing it with calcium carbonate [9][10][11][12] as filler. Considering that waste eggshells contain about 95% CaCO3 [13], more and more scientific studies report the possibility of using this biofiller as a source of calcium carbonate in various polymer matrices [6,[14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%